Persistence of Antibody and Cellular Immune Responses in Coronavirus Disease 2019 Patients Over Nine Months After Infection. (12th May 2021) - Yao, Lin; Wang, Guo-Lin; Shen, Yuan; Wang, Zhuang-Ye; Zhan, Bing-Dong; Duan, Li-Jun; Lu, Bing; Shi, Chao; Gao, Yu-Meng; Peng, Hong-Hong; Wang, Guo-Qiang; Wang, Dong-Mei; et al.
Abstract: Background: The duration of humoral and T and B cell response after the infection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remains unclear. Methods: We performed a cross-sectional study to assess the virus-specific antibody and memory T and B cell responses in coronavirus disease 2019 (COVID-19) patients up to 343 days after infection. Neutralizing antibodies and antibodies against the receptor-binding domain, spike, and nucleoprotein of SARS-CoV-2 were measured. Virus-specific memory T and B cell responses were analyzed. Results: We enrolled 59 patients with COVID-19, including 38 moderate, 16 mild, and 5 asymptomatic patients; 31 (52.5%) were men and 28 (47.5%) were women. The median age was 41 years (interquartile range, 30–55). The median day from symptom onset to enrollment was 317 days (range 257 to 343 days). We found that approximately 90% of patients still have detectable immunoglobulin (Ig)G antibodies against spike and nucleocapsid proteins and neutralizing antibodies against pseudovirus, whereas ~60% of patients had detectable IgG antibodies against receptor-binding domain and surrogate virus-neutralizing antibodies. The SARS-CoV-2-specific IgG + memory B cell and interferon-γ-secreting T cell responses were detectable in more than 70% of patients. Conclusions: Severe acute respiratory syndrome coronavirus 2-specific immune memory response persists in most patients approximately 1 year after infection, which provides a promising sign for prevention from reinfection and vaccination strategy. Abstract : SARS-CoV-2-specific antibody and memory T and B cell responses were detectable in most patients approximately 1 year after infection, indicating that durable immunity against secondary COVID-19 disease is possible in most individuals.